Measuring effective coverage of curative child health services in rural Burkina Faso: a cross-sectional study. Issue 5 (31st May 2018) - Koulidiati, Jean-Louis; Nesbitt, Robin C; Ouedraogo, Nobila; Hien, Hervé; Robyn, Paul Jacob; Compaoré, Philippe; Souares, Aurélia; Brenner, Stephan
Abstract : Objective: To estimate both crude and effective curative health services coverage provided by rural health facilities to under 5-year-old (U5YO) children in Burkina Faso. Methods: We surveyed 1298 child health providers and 1681 clinical cases across 494 primary-level health facilities, as well as 12 497 U5YO children across 7347households in the facilities' catchment areas. Facilities were scored based on a set of indicators along three quality-of-care dimensions: management of common childhood diseases, management of severe childhood diseases and general service readiness. Linking service quality to service utilisation, we estimated both crude and effective coverage of U5YO children by these selected curative services. Results: Measured performance quality among facilities was generally low with only 12.7% of facilities surveyed reaching our definition of high and 57.1% our definition of intermediate quality of care. The crude coverage was 69.5% while the effective coverages indicated that 5.3% and 44.6% of children reporting an illness episode received services of only high or high and intermediate quality, respectively. Conclusion: Our study showed that the quality of U5YO child health services provided by primary-level health facilities in Burkina Faso was low, resulting in relatively ineffective population coverage. Poor adherence to clinical treatment guidelines combined with the lack of equipment and qualified clinical staff that performed U5YO consultations seemed to be contributors to the gap between crude and effective coverage.